Hubungan Ekspresi IGF-1R dan HER-2 Terhadap Jumlah Mitosis dan Derajat Histopatologik pada Karsinoma Payudara Invasif Tidak Spesifik - Yessy Setiawati; Aswiyanti Asri; Rosfita Rasyid (Majalah Patologi Indonesia, 2020)
BackgroundThe IGF-1R signaling pathways have cross-talk with HER-2 signaling pathways and was thought to be one of the resistance mechanism intrastuzumab therapy. This research was proposed to analyze the correlation between IGF-1R and HER-2 expression with mitosis count andhistopathological grade in invasive breast carcinoma of no special type.MethodsThis research was a cross-sectional design. A total of fifty-five invasive breast carcinoma of no special type cases diagnosed in theAnatomical Pathology Centre Diagnostic of Medical Faculty of Andalas University in a period of 2014-2015 were collected and stainedimmunohistochemically with IGF-1R and HER-2 antibodies. IGF-1R and HER-2 expression were examined and their correlation with mitosiscount and histopathological grade were statistically analyzed with T-test, Oneway Anova and Chi-Square test.ResultsIGF-1R cytoplasm and membranous expression were found positive in 18.2% and 34.5% cases respectively, meanwhile, HER-2 expressionswere found positive in 23.6% cases of invasive breast carcinoma of no special type. There were significant correlations between IGF-1Rcytoplasm expression with mitosis count (p=0.049). There were no significant correlations between IGF-1R membranous expression withmitosis count (p=0.641) with histopathological grade (p=1.00). There were no significant correlations between HER-2 expression withmitosis count (p=0,495) and histopathological grade (p=1.000).ConclusionIGF-1R expressions have a significant correlation with mitosis count rather than HER-2 expressions. Inhibition it’s signaling pathways mayhave therapeutic value in breast carcinoma. Combination therapy of anti-HER-2 and anti-IGF-1R are expected to overcome resistance withtrastuzumab in HER-2 positive breast carcinoma